Enhancing Collaborative Learning Skills via Blended Problem-based Learning in Chemistry Learning - Atikah, Nurul; Ibrahim, Mohd Mokhzani; Jamaludin, Khairul Azhar; Tek, Ong Eng; Alias, Norlidah; Rosli, Mohd Shafie; Yahaya, Asmayati (CENTRAL ASIA AND THE CAUCASUS, 2022)
Poor mastery of three representation levels of Chemistry (macroscopic, microscopic and symbolic) has affected students’ academic performances. This is resulted from the traditional teaching that is teacher-centred and does not encourage students’ active participation. Potentially, Blended Problem–based Learning (BPBL) approach that integrates both face-to-face and online learning platforms focuses on students’ active involvement, especially collaborative skills (knowledge sharing, conflict resolution and reflective skills). Hence, the current study is aimed at exploring how BPBL can enhance these collaborative skills during learning activities in Chemistry learning. This study employed a qualitative approach - exploratory and explanatory case study. Through purposive sampling, two teachers and 20 students from two schools were selected. Data from observations, students’ documents and interviews were collected and analysed thematically. The findings suggested that BPBL approach can enhance the students’ collaborative learning experiences and skills. Firstly, the students demonstrated that they were able to share knowledge by: a) agreeing on the objectives of the problem, b) sharing what they have learned, and c) evaluating their info and others. Secondly, the students were able to resolve conflicts as they demonstrated their ability to: a) identify how the information is collected, and b) reevaluate their own information and of others. Lastly, the students were able to conduct reflection during the lessons as they: a) reflect and identify concepts that they struggle with, b) make generalization of the current findings to other relevant problems, c) reflect their overall action plan in solving the learning issues, and d) evaluate their own performance and of the group members throughout the learning process. In short, this study has provided valuable information on how BPBL can help enhance students’ collaborative learning skills during the teaching and learning process.